Calibration of the Neutral Current Detection Array in the SNO experiment - Cox, G; Cleveland, B; Di Marco, M; Evans, H; Guillian, E; Hallin, A; Huang, M; Howard, C; Jelley, N; Law, J; Loach, J; O'Keeffe, H; et al. (2011)
Since November 25th, 2004, the Sudbury Neutrino Observatory has been taking production data in its third and final phase. For this phase a 'Neutral-Current Detection (NCD) Array', consisting of 36 strings of 3He proportional counters and 4 strings of 4He proportional counters, was deployed in SNO's D 2O volume. It supplements the Cherenkov detector, consisting of 9456 photomultiplier tubes, present in the previous two phases by offering an independent measurement of the solar neutral current rate. The 3He counters detect neutrons from neutrino-deuteron neutral current interactions in the D 2O. We describe the calibration of this array. © 2011.